Place-based policies - How to do them and why - Jens Südekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
Place-based policies had a bad reputation for decades, if they received any attention at all. This has recently changed, for two reasons. First, many countries have experienced political backlashes from rising spatial economic disparities. Populist movements received the highest support in economically backward regions, which had been hit by severe local shocks. By trying to foster spatial economic cohesion, regional policies have become an attempt to insure against those political trends and to save liberal democracies altogether. Second, recent theoretical and empirical research has challenged the leading paradigm of spatial equilibrium analysis, according to which place-based policies are an inefficient interference into the market-based resource allocation. In this paper, I review those arguments and how their balance has changed over time. I argue that the demand for place-based policies is likely to increase in the future, as new digital technologies might reinforce urban-rural divides. But even if the general case for place-based policies now seems to be more widely accepted, the question remains what exactly should be done and which type of programs generate the highest return. Digging through the vast evaluation literature, I try to derive some robust lessons how to conduct place-based policies in practise.
Keywords: 330